Screenings of Four Medicinal Plants of Bangladesh for Bioactivities - Sikder, Md. Al Amin; Sharmin, Tasnuva; Rahman, AFM Mustafizur; Haque, Mohammad Rashedul; Rahman, Mohammad S; Rashid, Mohammad A (Dhaka University Journal of Pharmaceutical Sciences, 2013)
The methanol extracts of leaves of Nephelium lappaceum L., Pandanus foetidus Roxb., Ludwigia repens Rubin. and the whole plant of Adiantum philippense L. were subjected to assays of antioxidant, cytotoxic, thrombolytic and membrane stabilizing activities. The antioxidant activity was evaluated by DPPH free radical scavenging activity using butylated hydroxytolune and ascorbic acid as standards. The crude extract of N. lappaccam exhibited the highest free radical scavenging activity (IC50= 3.93±0.25?g/ml). On the other hand, the crude methanol extracts of A. philippense and P. foetidus demonstrated significant brine shrimp lethality with LC50 values 0.50±0.84 ?g/ml and 0.58±0.73 ?g/ml, respectively as compared to the standard anti-neoplastic drug, vincristine sulfate (LC50= 0.45 ?g/ml). Weak thrombolytic activity was observed for the test samples. The crude methanol extracts of P. foetidus and N. lappaceum showed 17.31±0.82 % and 17.29±0.91 % clot lysis while standard streptokinase and water, used as positive and negative controls, demonstrated 66.77 % and 3.79 % lysis of clot, respectively. The methanol extract of whole plant of A. philippense inhibited hypotonic solution and heat induced haemolysis of RBCs by 53.09±1.01 % and 35.36±1.60 % as compared to 71.77 % and 42.20 % by acetyl salicylic acid, respectively. Dhaka Univ. J. Pharm. Sci. 12(1): 59-62, 2013 (June) DOI: http://dx.doi.org/10.3329/dujps.v12i1.16301